Flipped learning in medical education: Enhancing engagement through innovative pedagogy - Mehrdad Nazarieh; Mozhdeh Delzendeh; Amin Beigzadeh (Research and Development in Medical Education)
Flipped learning has emerged as an innovative instructional approach in medical education, transforming traditional teacher-centered models into dynamic, learner-centered environments. This pedagogical strategy involves students engaging with instructional content outside the classroom, followed by interactive activities during class time, thereby enhancing student engagement and promoting active learning. Grounded in educational theories such as Constructivism and Adult Learning Theory, flipped learning facilitates knowledge construction through pre-class engagement and fosters self-directed learning, particularly relevant for adult learners in medical fields. Successful implementation requires meticulous design of instructional strategies, high-quality pre-class materials, and engaging in-class activities that promote collaboration and critical thinking. Assessment methods must also adapt to this framework, utilizing formative assessments to gauge understanding and encourage continuous improvement. Additionally, faculty development initiatives are essential for equipping educators with the skills necessary to implement this approach effectively. Flipped learning not only improves student performance but also cultivates a supportive learning atmosphere, fostering critical thinking and communication skills. This article advocates for the evaluation of flipped learning programs using the CIPP model to assess their effectiveness and guide future innovations in medical education.